Research of affordability to essential medicines for coronary heart disease in Ukraine - Natalia Bilousova; Natalia Tkachenko; Nataliia Kozhuharyova; Maryna Dolzhenko (Journal of Pharmaceutical Policy and Practice)
Background The issue of population access to medicines is relevant worldwide. Pandemics, natural disasters, wars negatively affect the population's access to medicines, as emphasised by the WHO and the UN.Methods The analysis of scientific publications in the Ukrainian scientometric databases (NRAT, OUCI); Scopus, Web of Science, Pubmed, Medline, BMJ and Embase; the legal field for providing medical care to patients with CHD and comorbid conditions and its pharmaceutical component. The EML of Europe and Ukraine are compared; the clinical recommendations and pharmacotherapy of European/American Societies of Cardiology (ESC/AHA) and Ukrainian for patients with CHD and comorbid conditions are compared.Results The prices of medicines that are not part of the ‘Affordable Medicines’ program and are included in the EML lists were analysed; their availability for Ukrainian patients in wartime conditions was determined. The legal field of providing medical care to patients with CHD and comorbid conditions has been formed. It was established that not all medicines specified in the EML are registered on the territory of Ukraine and included in the Program of Medical Guarantees (PMG).Conclusion The PMG includes most of the EML medicines. The modern pharmacotherapy of CHD and comorbid conditions has a positive impact on the budget of the health care system in clinical practice proposed by the ESC/AHA was determined. The lists of medicines in the PMG in Ukraine, need to be revised on the basis of the Health Technology Assessment for further inclusion in the state program ‘Affordable Medicines' for long-term use by patients with CHD and comorbid conditions. These measures will improve the quality of pharmaceutical care for these patients.